2009
DOI: 10.1177/0018720809341735
|View full text |Cite
|
Sign up to set email alerts
|

Using Peripersonal Warning Signals to Orient a Driver’s Gaze

Abstract: Warning systems that have been designed around the constraints of the human brain offer great potential in the future design ofmultisensory interfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
1
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 34 publications
2
45
1
1
Order By: Relevance
“…In this 25-minutes experiment, only the forward head position condition (see Ho & Spence, 2009) was presented. The participants had to depress the brake pedal as rapidly as possible whenever they detected the sudden closing-in on the lead car in the video clips.…”
Section: Design and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…In this 25-minutes experiment, only the forward head position condition (see Ho & Spence, 2009) was presented. The participants had to depress the brake pedal as rapidly as possible whenever they detected the sudden closing-in on the lead car in the video clips.…”
Section: Design and Proceduresmentioning
confidence: 99%
“…In particular, recent empirical evidence suggests that the presentation of non-visual warning signals in a driver's peripersonal space (i.e., close to, or on, the driver's body) may represent a unique means of communicating behaviorally relevant stimuli that demand the driver's immediate attention (see Ho & Spence, 2009). Many researchers have focused their efforts on trying to identify specific properties of warning signals that define their effectiveness in terms of eliciting speeded and appropriate behavioral responses from drivers for collision avoidance.…”
Section: Introductionmentioning
confidence: 99%
“…One such recent example is by Ho and Spence (2009) who predicted that behavioral responses by drivers to in-car warning signals will be facilitated by designing warning systems that incorporate insights about constraints of the brain. Drawing on neuroscientific findings that humans (and other animals) pay greater attention and respond more rapidly to sensory stimuli occurring in peripersonal (i.e., close to the body) than extrapersonal space, they find support for the idea that peripersonal warning signals, compared with traditional warning signals, afford significant performance advantages.…”
Section: Hypothesis Generation and Constraintsmentioning
confidence: 99%
“…First studies have demonstrated the positive effect of these peripheral visual signals in driving (see, e.g., Henning et al, 2008;Ho & Spence, 2009;Kienast et al, 2008;Mahlke, Rösler, Seifert, Krems, & Thüring, 2007). In these studies, LEDs situated at the bottom of the front window of the car (e.g., Henning et al, 2008;Mahlke et al, 2007) or close to the side mirrors (Wolkenstein, 2005) were used.…”
Section: Abstract Attention Allocation Visual Scan Strategies Drimentioning
confidence: 99%